Interorganizational Networks: Fundamental to the Accreditation Canada Program. Issue 3 (October 2014) - Mitchell, Jonathan I.; Nicklin, Wendy; MacDonald, Bernadette
Within the Canadian healthcare system, the term population-accountable health network defines the use of collective resources to optimize the health of a population through integrated interventions. The leadership of these networks has also been identified as a critical factor, highlighting the need for creative management of resources in determining effective, balanced sets of interventions. In this article, using specific principles embedded in the Accreditation Canada program, the benefits of a network approach are highlighted, including knowledge sharing, improving the consistency of practice through standards, and a broader systems-and-population view of healthcare delivery across the continuum of care. The implications for Canadian health leaders to leverage the benefits of interorganizational networks are discussed.